Investigating the Aroma Chemistry of Dendrobium Stems (Chinese Name: Shihu) - Kirkwood, Aidan (2025)
People have consumed dried Dendrobium stems, known in China as Shihu, for thousands of years as food and traditional medicine. Shihu is valued for its potential health benefits and flavour attributes, and for this reason, it is well integrated into traditional Chinese cooking, and more recently, become a modern ingredient in nutraceutical drinks. Shihu contains a diverse range of volatile compounds and glucomannan polysaccharides. However, there are gaps in the knowledge of the compounds responsible for its aroma and their formation, and this thesis aims to investigate these important compounds through: 1) comprehensively investigating the aroma compounds of Dendrobium stems, focusing on 2) key aroma-active compounds, 3) assessing drying's impact on aroma formation and 4) evaluating flavour stability. Instrumental analysis was used to characterise and semi-quantify volatile aroma compounds, identify those responsible for the aroma, quantify flavour precursors, and evaluate aroma stability. Gas Chromatography-Mass Spectrometry (GC-MS) identified 21 aroma compounds in commercially available dried Shihu. Varying oven drying temperatures and durations impacted both the aroma compounds and moisture content (Chapter 3). Although the drying process resulted in a 28.45 % reduction in glucomannans, the research primarily focused on flavour. GC-O (Olfactometry) analysis with 13 panellists indicated nine aroma compounds were aroma-active in dried stems (including 1-octen-3-one and 4-oxoisophorone)(Chapter 4). Carotenoids, amino acids, and monosaccharides were quantified using three Liquid Chromatography techniques, linking precursor loss during drying to aroma-active compound formation (Chapter 5). Shelf life testing indicated no significant changes in aroma-active compounds during storage (20-30 °C for 12 weeks), but higher storage temperatures caused further precursor degradation (Chapter 6). Multivariate analysis indicated aroma compounds as markers of storage and temperature mismanagement. This research provides a mechanistic understanding of flavour generation during Shihu drying, applicable to other plants with similar chemistry. Awareness of important aroma compounds and their changes during storage has the potential to improve product quality and enhance the global popularity of Shihu.